IMPLEMENTING LEARNING COMMUNITY STRATEGY TO IMPROVE STUDENTS SPEAKING ABILITY IN JUNIOR HIGH SCHOOL - Nur Ainun Siregar; Desvalini Anwar (Universitas Negeri Padang, 2018)
This paper was aimed to explain the use of Learning CommunityStrategyin learning speaking for Junior High School. In this paper was explained how Learning Communityimproved students’ ability for Junior High School. Speaking is one of skills needs to be comprehended by students, but there are many problems in learning process. Therefore, Learning Communitybecame a good method for teacher to use in learning speaking. In Learning Community, learning activities was done in groups . The students was divided into groups in order to know each other to assess their cooperation in Learning Community. It is not only developing the students’ social life, but also building a good relationship between students and teacher especially in speaking English.